(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: The aim of the study is to compare hyponatremia as a complication of treatment with terlipressin and octreotide in patients having severe gastrointestinal bleed due to portal hypertension. Materials and Methods: This randomized controlled trial was conducted at Department Of Medicine Mayo hospital, King Edward Medical University Lahore. 60 patients were divided into two groups randomly by taking 30 patients in Group-A who received Terlipressin 1 mg 6 hourly and same no. of patients in Group-B who received Octreotide 50 microgram per hour IV infusion both for 5 days. Daily electrolyte monitoring was done to see the Hyponatremia as the complication of the treatment. Results: The mean age in group-A was 41.46 ± 8.58 years and in group-B the mean age was 44.20 ± 5.01 years. In group-A there were 17 (56.67%) male and 13 (43.33%) female patients while in group-B there were 12 (40%) male and 18 (60%) female patients. Hyponatremia was higher in group A, i.e. in 15(50%) patients as compared to group-B i.e. 4(13%) patients, p-value = 0.002. Conclusion: In the light of these results it can be concluded that octreotide is a better treatment option than terlipressin in patients with upper gastrointestinal bleeding secondary to portal hypertension as far as hyponatremia is concerned because the acute decrease in serum concentration of sodium is more common in the later one.